Proverbialismos: as mensagens de sabedoria em tempos de redes sociais - Rocha, José Marcos Viegas (2016)
This work's object of study are compositions between proverbs and images disseminated by users of the Internet social network, Facebook. The aim consists in analysis of the corpus to comprehend the singularities of the signic framing of these objects in its media ambience. The justification lies in the fact that social networks progressively grow as the complexity of communication processes just as it increases the number of users and cyber activity mechanisms. This demonstrates relevance to the area of Communication. As problematic, it is understood that the combination between proverbs and images on Facebook establishes presence motivated by didactic, philosophical and aesthetic intentions, but is also part of the composition of an identity on the social network. The first chapter contains traditional definitions of proverb, considering its multiplicity of forms and characteristics. Following, it is displayed a set of structural theories and consecrated analysis by linguists and semioticians (Coseriu, Greimas, Zuluaga, Cândido, Pires Ferreira). Also, as this is not only the study of traditional proverbs, but, indeed, compositions between text and image conveyed in a cyber social network, there are also some concepts and theories about visual language (Flusser, Greimas, Volli). The second chapter presents theories and concepts of digital ambience (Flusser, Lévy) as well as factual information regarding the social network Facebook and its interaction mechanisms. The third chapter analyzes a corpus made up of fifteen (15) compositions "proverbs-images." These analysis mainly conform concepts of discursive semiotic (Greimas), since the idea is to remark the sense relations that are established between the proverbial message and choosen image, highlighting its semantic and formal processes